2010
DOI: 10.1371/journal.pone.0008750
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Mutations Decrease Sensitivity of Gene Expression to Random Environmental Variation in Caenorhabditis elegans

Abstract: BackgroundBiological phenotypes are described as “canalized” if they are robust to minor variation of environment and/or genetic background. The existence of a robust phenotype logically implies that some underlying mechanism must be variable, in the sense of “able to vary”, in order to compensate for variation in the environment and/or genetic effects. Several lines of evidence lead to the conclusion that deleterious mutations predictably render morphological, developmental, and life-history traits more sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
2
3
Order By: Relevance
“…Although the results of this study and results from other studies involving C. elegans [60], [61] and Drosophila [62] clearly show that strong and significant results can be detected with a small number of MA lines, there are several reasons why the failure to detect a strong relationship between oxidative stress and the frequency of base substitutions should not be surprising. First, the measures of oxidative stress reported here were measured at the endpoint of 250 generations of evolution under relaxed selection, whereas mutations accumulated in the genome over the entire 250 generations.…”
Section: Discussioncontrasting
confidence: 63%
“…Although the results of this study and results from other studies involving C. elegans [60], [61] and Drosophila [62] clearly show that strong and significant results can be detected with a small number of MA lines, there are several reasons why the failure to detect a strong relationship between oxidative stress and the frequency of base substitutions should not be surprising. First, the measures of oxidative stress reported here were measured at the endpoint of 250 generations of evolution under relaxed selection, whereas mutations accumulated in the genome over the entire 250 generations.…”
Section: Discussioncontrasting
confidence: 63%
“…As with the mutational variance, this suggests that mutations resulting in increased sensitivity to environmental and transcriptional noise due to dysregulation of gene expression are accumulating to the greatest degree under conditions of extreme genetic drift, and to a lesser degree in MA lines with larger population bottlenecks (and greater efficiency of selection). This increase in the Vr for transcription in our MA lines contrasts with a previous C. elegans study using DNA microarrays in which the ancestral N2 control was found to have higher Vr than the MA lines (Baer and Denver 2010). The observation that an increase in Vr largely mirrors the pattern for Vm suggests that the two may be related and perhaps stem from the same mechanistic causes.…”
Section: Discussioncontrasting
confidence: 96%
“…This suggests that new mutations have rendered transcriptional regulation of some genes less robust and perhaps more sensitive to environmental variation. This contrasts with a previous C. elegans study in which the ancestral N2 control was found to have higher Vr than the MA lines (Baer and Denver 2010).…”
Section: Greater Mutational and Residual Variance At Small Population Sizecontrasting
confidence: 99%
See 2 more Smart Citations